TWELVE ASPECTS OF PAKEM PADALANGAN WAYANG GOLEK PURWA SUNDA: CONCEPTUAL FOUNDATIONS ACCORDING TO MAS ATJE SALMOEN - Maulana, Marsel Ridky (Pusat Penerbitan LP2MPP ISI Bali, 2025)
This study aims to examine the pakem of Sundanese wayang golek purwa as formulated and documented by Mas Ace Salmun, a prominent figure in the codification of this traditional art form. As a cultural heritage of the Sundanese people, wayang golek purwa embodies profound philosophical values, with the pakem serving as the primary guideline in its performance. This research explores the principles of pakem in the art of padalangan according to Ace Salmun’s perspective on wayang golek purwa performances. The study employs a qualitative approach with a literature review method, tracing classical sources and textual documentation that specifically discuss pakem in wayang golek purwa. The findings reveal that Ace Salmun identifies twelve fundamental aspects of pakem padalangan, namely: Awi-Carita, Amardi-Basa, Anta-Wacana, Amardawa-Lagu, Parama-Kawi, Parama-Sastra, Kawi-Radya, Renggep, Sabet, Banyol, Engés, and Tutug. These twelve aspects function as a conceptual foundation that enables a structured analysis of Sundanese wayang golek purwa padalangan practice. This research is expected to enrich the body of literature on cultural and traditional performing arts studies while also contributing to the preservation of Sundanese wayang golek purwa. Accordingly, the study holds significance not only for academics but also for practitioners particularly dalang and broader communities concerned with safeguarding Sundanese cultural heritage.